Music teachers' lives and the micropolitical landscape of schools. (June 2018) - Conway, Colleen; Hibbard, Shannan
The purpose of this study was to examine how four experienced music teachers describe their navigation of the micropolitical landscape in their schools. Research questions included: (a) How do the teacher participants describe their strategies used to navigate the political, contextual, and interpersonal landscape of their schools and school communities?, and (b) How do participants perceive the influence of the micropolitical landscape on their own workplace experiences as well as the classroom experiences of their students? Drawing from case study and narrative design frameworks, the study data included an email survey, an observation of each teacher, two individual interviews with each teacher, an interview with the school principal for each teacher and a focus group interview with teachers at the end of the project. Findings highlight the purposeful nature of experienced teacher micropolitical interactions.